Capital expenditure, tax avoidance and bank performance: Evidence from Jordanian banks - Mohammad Fawzi Shubita; Nahed Habis Alrawashedh; Duaa Fawzi Shubita; Ahmed Dheyauldeen Salahaldin (Investment Management & Financial Innovations)
Tax avoidance and capital expenditure are critical financial strategies employed by banks to enhance profitability. Understanding their impact on bank financial performance is essential for policymakers and bank managers seeking to optimize financial strategies. This study is aimed to investigate the influence of tax avoidance (TAV) and capital expenditure on the financial performance of Jordanian banks, while exploring the moderating effect of firm size. Using regression analysis, the relationships between tax avoidance, capital expenditure, bank size, and bank financial performance were investigated. Financial data from Jordanian banks were utilized over a specified period. The study results refer that tax avoidance has a positive correlation with ROA (the correlation = 31.7%) and ROE (the correlation = 30.2%). The results reveal that tax avoidance significantly impacts bank financial performance, with banks employing tax avoidance strategies exhibiting higher returns on assets and equity. However, capital expenditure does not demonstrate a significant association with bank financial performance. Additionally, firm size does not moderate the link between TAV, capital expenditure, and bank financial performance. The non-significant impact of capital expenditure underscores the need for banks to explore alternative avenues for improving financial performance. These findings provide a valuable insight for policymakers and bank managers in devising effective financial strategies to optimize bank performance in the Jordanian context.